(untitled) (Kinesiology, 2019)
Custom-made mouthguards are used to prevent orofacial injuries arising from falls and knocks. It has been observed that thicker custom-made mouthguards transmit less force to the mouth owing to their higher energy absorption capacity. However, it is believed that thicker custom-made mouthguards can alter ventilation during exercise because of the higher resistance or restriction of oral airflow. The purpose of this study was to investigate if a thicker custom-made mouthguard (occlusal thickness of 5-mm; 5MG) alters ventilatory parameters, rate of perceived exertion (RPE), and peak velocity during an incremental test relative to a thinner custom-made mouthguard (occlusal thickness of 3-mm; 3MG) and no mouthguard (NoMG). Eleven male amateur contact team sports players completed three running incremental tests on different days, with each test performed with 3MG, 5MG, and without a mouthguard. The peak velocity during the incremental test was similar between the different conditions (14.9 ± 0.6, 14.9 ± 0.7, and 14.7 ± 0.9 km.h-1 for NoMG, 3MG, and 5MG, respectively). Furthermore, no differences were found in the peaks of pulmonary oxygen uptake, minute ventilation, and respiratory frequency, as well as second ventilatory threshold. RPE was higher when wearing 5MG than when running without a mouthguard only at the 12.5 km.h-1 stage (P = .03). These data indicate that wearing custom-made mouthguards with occlusal thicknesses between 3- and 5-mm does not alter ventilatory parameters at the end of an incremental test. Thus, custom-made mouthguards with an occlusal thickness of 5-mm should be preferred owing to their greater protection capacity.